Canada : Report on the Observance of Standards and Codes. (IMF Staff Country Reports; Country Report, 2014)
This paper discusses key findings of the Report on the Observance of Standards and Codes for Canada. Canada has a very high level of compliance with the Basel Core Principles for Effective Banking Supervision. In response to the challenges and structure of its market, the Canadian banking supervisor (OSFI) has developed and is a strong proponent of risk-based, proportionate, supervisory practices and applies a 'close touch' approach to its supervised entities. The supervisory approach is well structured, forward looking and maintained on as dynamic a basis as possible. Entry to the Canadian market is subject to demanding prudential entry standards.